CCNA routing and switching : study guide - Lammle, Todd (Sybex, 2013)
Prepare for the new CCNA exams with this Todd Lammle study guide. Cisco author, speaker, and trainer Todd Lammle is considered the authority on all things networking, and his books have sold almost a million copies worldwide. This all-purpose CCNA study guide methodically covers all the objectives of the ICND1 (100-101) and ICND2 (200-101) exams as well as providing additional insight for those taking CCNA Composite (200-120) exam. It thoroughly examines operation of IP data networks, LAN switching technologies, IP addressing (IPv4/IPv6), IP routing technologies, IP services, network device security, troubleshooting, and WAN technologies. Valuable study tools such as a companion test engine that includes hundreds of sample questions, a pre-assessment test, and multiple practice exams. Plus, you'll also get access to hundreds of electronic flashcards, author files, and a network simulator.